Multiple cardiometabolic diseases enhance the adverse effects of hypoalbuminemia on mortality among centenarians in China: a cohort study - Haowei Li; Shengshu Wang; Shanshan Yang; Shaohua Liu; Yang Song; Shimin Chen; Xuehang Li; Zhiqiang Li; Rongrong Li; Yali Zhao; Qiao Zhu; Chaoxue Ning; et al. (Diabetology & Metabolic Syndrome, 2023)
Abstract Background Although hypoalbuminemia was associated with high risk of mortality in community-dwelling older adults, as well as in the hospitalized older adults, little is known among centenarians. And there are limited data on whether having cardiometabolic diseases (CMDs) is associated with additive effects. Methods Baseline examinations including a determination of albumin levels were performed in 1002 Chinese centenarians from January 2014 through to December 2016, and the survival status was subsequently ascertained until 31 May 2021. Cox proportional risk model was performed to assess the risk of all-cause mortality associated with albumin levels and hypoalbuminemia combined with CMDs. Results Of 1002 participants included in the analysis, the mean level of albumin was 38.5 g/L (± standard deviation, 4.0 g/L), and 174 (17.4%) had hypoalbuminemia (albumin < 35 g/L). The multivariable analyses showed that albumin level was negatively associated with all-cause mortality (P trend < 0.05). Compared to normoalbuminemia, hypoalbuminemia was associated with an increased mortality risk in the overall participants (hazard ratio [HR]: 1.55, 95% confidence interval [CI]: 1.22–1.97). Furthermore, the HR (95% CI) of hypoalbuminemia combined with multiple CMDs was 2.15 (1.14–4.07). There was evidence of an additive deleterious dose effect of an increasing number of CMDs (P trend = 0.001). Conclusions Hypoalbuminemia is associated with an increased risk of all-cause mortality in Chinese centenarians, and this risk is more pronounced among centenarians with multiple cardiometabolic diseases. Our findings suggest that older adults with hypoalbuminemia, especially comorbid multiple CMDs warrant early identification and management.